PINTU BUKA TUTUP OTOMATIS PADA JALUR BUSWAY BERBASIS MIKROKONTROLER - , IRFAN GHOZALI M; , Budi Bayu Murti, ST., MT. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Orderly traffic is a very important component in everyday life - particularly in terms of the driving motor vehicle on public streets . But in reality many traffic violations that cause congestion and inconvenience to other road users . Especially in Jakarta busway lane , a lot of vehicles entering the busway lane resulting in congestion and inconvenience to passengers busway for causing congestion so that the travel time becomes longer . The purpose of this system is made to provide comfort and enforcement of traffic rules for road users who break the busway lane . In this system , the tool will detect and will work only when the busway is in front of the door within a certain distance . This means that other vehicles can not pass through the automatic doors . To operate, this tool menguunakan multiple inputs and outputs including color sensors, servo motors, and infrared sensors. The sensor will detect the color of the existing color code in the body of the busway is not owned by another vehicle . This color sensor as an input to drive the servo motor in an open door and an infrared sensor as an input to drive the servo motor in the closing state. The movement of the servo motor is limited to the range 0 Ë - 180 Ë. Infrared sensors can detect objects at the farthest distance of 80 cm.